Psychological impacts of intervention to improve a therapeutic garden for older adults with dementia: a case study conducted at a care facility - Meneghetti, Chiara; Murroni, Veronica; Borella, Erika; Melendugno, Andrea; Carbone, Elena; Goldin, Giulia; Cavalli, Raffaele; Basso, Andrea; Pazzaglia, Francesca (Frontiers in Psychiatry, 2023)
Introduction: Exposure to nature is known to support psychological well-being, and can support People with Dementia (PwD). Here we describe a case study conducted at a care facility for PwD to examine the effect of their exposure to nature after intervention to renovate an existing Therapeutic Garden (TG). Changes in frequency of attendance and behavior in the TG were examined. A single case was also considered to assess individual benefits. Materials and methods: Twenty-one PwD participated in the study. Their behavior in the TG was observed for 4 weeks before and after the intervention (using behavioral mapping), and measures of individual characteristics (general cognitive functioning, behavioral/neuropsychiatric symptoms, depression, and quality of life) were administered. Results: Ten of the 21 PwD visited the TG more often after the intervention, their social behaviors (e.g. talking to others) increased, and their active isolated behavior in the garden (e.g. smelling, touching flowers) tended to increase. The increase in social behavior related to less severe baseline depressive symptoms. Passive isolated behaviors related to more impaired baseline cognitive functioning. The case of Mrs. A extended the findings for the whole sample: although her dementia symptoms (apathy, motor disturbances) worsened, she visited the TG more often after the intervention, her social exchanges and active isolated actions increased, and her agitation and wandering decreased. Discussion: These results support the benefits of exposure to nature for PwD, and underscore the importance of considering users’ profiles to optimize their use of a TG.